Performance Test Base On PC With RouterOS RouterOS On Board - Putra, Willy Permana (Universitas Ahmad Dahlan, 2017)
In this era of technology now a lot of RouterOS on Board that offers multiple features and functions to networking needs. In the development of RouterOS on Board be preferred due to the more simple and more efficient, in terms of price is also not too relatively expensive no wonder a lot of interest and preferred. RouterOS on Board is widely used in several companies and the education community.Mikrotik is a common tool used to connect to the network, the proxy did some breakthrough is making hardware and software related to the computer network system. As we know MikroTik RouterOS™ is an operating system that can be used to make computer router reliable network is among others includes various features made by proxy, such as Routing - Static Routing, Hotspot, Simple Tunnels, Web Proxy, DHCP, VRRP, NTP, SNMP, MNDP, Firewall and NAT and others.This is what the basis of this research on the endurance test on Board with RouterOS RouterOS Base on PC and this study using MikroTik RouterOS™ as test equipment, later to be tested from both components are to see to what extent the network deal with activating Features- features. From the experimental results are later expected gain new knowledge that the tools are suitable for use in handling network.